ANALISIS PERTANGGUNGJAWABAN PENGELOLAAN DANA DESA NAGORI SINAR BARU KECAMATAN SILIMAKUTA KABUPATEN SIMALUNGUN - Girsang, Indah Rehlita; Purba, Imelda Rimenda; Naibaho, Pani Romauli Elisabet (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to determine how accountability of village fund management in improving village development in Sinarbaru village, Silimakuta District, Simalungun Regency. The population in this study is the Budget Report and Realization of Nagori Sinarbaru Village Fund for the year 1975-2023, the sample in this study is the Budget Report and Realization of Sinarbaru Village Fund for 2018-2022. Data collection techniques in this study were carried out by interview, observation and documentation techniques. The data analysis technique used in this study is qualitative descriptive. The results showed that the accountability of the Village Fund includes Transparency, Accountability and Participation. The accountability carried out by the Village Government of Nagori Sinarbaru, Silimakuta District, Simalungun Regency has followed the rules set out in the legislation. However, the process is not yet optimal. This can be seen from the transparency process where the community has not been able to access incoming and outgoing cash, so that the community cannot eval_uate the work of the village government.